HA-JOON CHANG AND AMARTYA SEN, TWO CONCEPTIONS OF DEVELOPMENT: THE ROLE OF THE STATE AND THE EXPANSION OF INDIVIDUAL LIBERTIES - Souza, Ana Luiza da Gama e (Juris Poiesis - Qualis A3, 2021)
This article presents the conceptions of development formulated by Ha-Joo Chang and Amartya Sen aiming to evaluate how they account to face the great challenges caused by the expansion of a global economic market. Chang and Sen propose different alternatives for understanding the notion of development. The first one builds a historical critique through which he intends to show the importance of the role of the State for economic development, in opposition to liberal and neoliberal recommendations in favor of free trade and non-intervention. The second is concerned with the deepening of social inequalities, on the one hand, and, on the other, the increase in wealth and accumulation, the development of technology and science, the consolidation of democracy and human rights, and formulates an extensive notion of human development focused on the agent, the individual, and the expansion of his freedom considered as a social commitment that makes it possible to face these deprivations. Both perspectives refute the argument that liberal policies are the only means of leading to development. However, Chang relies on historical evidence of protectionism as a political practice to counter this argument, reaffirming the role of the state, whilst Sen proposes a way to assess the various inequalities, empirically inferred, from the comprehensive analysis of the economy, social and political institutions, involving a multiplicity of institutions and actors beyond the state.